A methodology to promote business development from research outcomes in food science and technology - Eduardo L. Cardoso (International Journal of Food Studies)
Valorization of knowledge produced in research units has been a major challenge for research universities in contemporary societies. The prevailing forces have led these institutions to develop a “third mission”, the facilitation of technology transfer and activity in an entrepreneurial paradigm. Effective management of challenges encountered in the development of academic entrepreneurship and the associated valorization of knowledge produced by universities are major factors to bridge the gap between research and innovation in Europe. The need to improve the existing institutional knowledge valorization processes, concerning entrepreneurship and business development and the processes required were discussed. A case study was designed to describe the institutional knowledge valorization process in a food science and technology research unit and a related incubator, during a five year evaluation period that ended in 2012. The knowledge valorization processes benefited from the adoption of a structured framework methodology that led to ideas and teams from a business model generation to client development, in parallel, when possible, with an agile product/service development. Although academic entrepreneurship engagement could be improved, this case study demonstrated that stronger skills development was needed to enable the researcher to be more aware of business development fundamentals and therefore contribute to research decisions and the valorisation of individual and institutional knowledge assets. It was noted that the timing for involvement of companies in the research projects or programs varied with the nature of the research.